2020
DOI: 10.20344/amp.12083
|View full text |Cite
|
Sign up to set email alerts
|

Perfeccionismo, Burnout e as Atividades Extracurriculares nos Estudantes de Medicina da Universidade de Coimbra

Abstract: Introduction: The participation in extracurricular activities reduces the attributed importance to some causes of perfectionism, which influences the prevalence of burnout in medical students. This study aimed to investigate how this relationship occurs and which factors it is dependent on, in order to create strategies directed at these potential targets.Material and Methods: We developed a questionnaire that assesses the participation in extracurricular activities, including a survey regarding the reasons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
1
11
0
2
Order By: Relevance
“…Most students participated in E.A. (76.7%), in a higher proportion than previously reported [9,12] with a preference for the "Individual Physical/Sports" activity with 49.4%, a lower value than previously reported [11,12]. "Volunteering and Social Services" was reported by (18.7%), obtained a value higher than that already observed for medical students [11], but lower than that already observed in Dentistry and Pharmaceutical Sciences [12,13].…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Most students participated in E.A. (76.7%), in a higher proportion than previously reported [9,12] with a preference for the "Individual Physical/Sports" activity with 49.4%, a lower value than previously reported [11,12]. "Volunteering and Social Services" was reported by (18.7%), obtained a value higher than that already observed for medical students [11], but lower than that already observed in Dentistry and Pharmaceutical Sciences [12,13].…”
Section: Discussionmentioning
confidence: 59%
“…Studies report that students participation in E.A. can improve teamwork skills, networking, better time management, helping others and contact with people of different perspectives, acquiring new knowledge, and expanding the individual curriculum [9,12,13]. Reports also exist stating that improvement of stress management capacity was indicated as an effective coping mechanism in stress management [11], physical activities being related to low levels of stress [10], and Volunteering and Social Services promoting solidarity, social responsibility, and a sense of community [10].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this dominance is due to the ease of quantitative measurement of PA in terms of time and intensity and the positive effects of PA on health (31). A study involving 360 medical students determined that 53.9 % of the students participated in extracurricular activities, and participation in extracurricular activities was associated with a low prevalence of burnout, regardless of the chosen activity (32). BDI and BAI scores of our participants were lower in those who had a long-term active hobby (49.4 %) and participation in at least one sports activity (46.6%), but without statistical significance in the BDI scores of those who participated in at least one sports activity.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, outras pesquisas sugerem prevalências maiores, em Portugal (22.2%) (Dinis et al, 2020), Hong Kong (27.9%) (Lee et al, 2020), Estados Unidos (34.1%) (Cooket al, 2014) e Malásia (36.8%) (Daud et al, 2020). Estudos do Paraguai e do Equador, respectivamente, observaram prevalências de 9% (González-Escobar et al, 2020) e 88% (Pire et al, 2020).…”
Section: Discussionunclassified